2012
DOI: 10.1007/s12149-012-0660-x
|View full text |Cite
|
Sign up to set email alerts
|

The current status of an FDG-PET cancer screening program in Japan, based on a 4-year (2006–2009) nationwide survey

Abstract: ObjectiveThe aim of this study was to survey the 18F-fluorodeoxyglucose-positron emission tomography (FDG-PET) cancer screening program conducted in Japan.MethodsThe “FDG-PET cancer screening program” included both FDG-PET and positron emission tomography with computed tomography (PET/CT) with or without other combined screening tests that were performed for cancer screening in asymptomatic subjects. A total of 155,456 subjects who underwent the FDG-PET cancer screening program during 2006–2009 were analyzed.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 18 publications
4
42
1
2
Order By: Relevance
“…In the so far largest 18 F-FDG PET screening study performed at 233 facilities with inclusion of 155,456 subjects, positive 18 F-FDG PET findings suggesting possible cancer were found in 10.9% of the cases. However, on the basis of further investigations the true-positive (TP) rate (positive predictive value) was only 32.3% (26). Accordingly, this large-scale study clearly demonstrated that 18 F-FDG PET had a far-too-high FP rate to be applied as screening of the general population.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…In the so far largest 18 F-FDG PET screening study performed at 233 facilities with inclusion of 155,456 subjects, positive 18 F-FDG PET findings suggesting possible cancer were found in 10.9% of the cases. However, on the basis of further investigations the true-positive (TP) rate (positive predictive value) was only 32.3% (26). Accordingly, this large-scale study clearly demonstrated that 18 F-FDG PET had a far-too-high FP rate to be applied as screening of the general population.…”
mentioning
confidence: 71%
“…In a previous study of 18 F-FDG PET as the primary imaging modality, which was performed in a low-prevalence (1%) population, it was clearly demonstrated that 18 F-FDG PET was of limited value because of the high FP rate (26). However, in the recently established nationwide DOCs in Denmark, the prevalence of cancer is much higher and around 16%-18% (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, although 2-[ 18 F]fluoro-2-deoxyglucose (FDG) positron emission tomography (PET), including PET combined with CT (PET/CT), has been increasingly used to screen patients for whole-body cancers, including CRC [9][10][11], the sensitivity of FDG-PET in CRC screening has not been fully analyzed. FDG-PET is a noninvasive functional imaging modality that reflects the change in glucose metabolism in tumor cells, and has been applied in oncology [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use for cancer screening in general population was still under debate because many benign lesions such as supraclavicular fat pads, nodular goiter, and benign prostatic hypertrophy could also be shown as high uptakes. It could lead to unnecessary and potentially invasive investigations with extra cost, risks, and anxiety to patients [34].…”
Section: Limitations Of Pet-ctmentioning
confidence: 99%